(untitled) (Perner’s Contacts, 2010)
High sensitive commodities quality assurance is presently more difficult task for transport, storage and maniplation activities than for individual producent. This report shortly describes the principles that should be keept in logistics activities and transport of living flowers and plants. Because of their characteristics they belong into pervertibel goods.